Uncertainty of Oil Proved Reserves and Economic Growth in Iran - Asadi Mehmandosti, Elaheh; Bazzazan, Fatemeh; Mousavi, Mir Hossein (International Journal of Energy Economics and Policy, 2016)
The relationship between the oil and the level of economic activity is a fundamental empirical issue in macroeconomics. Also, a part of major debates between the pessimists and the optimists approaches about economic growth is how uncertainty of proved reserves of non- renewable energy resources as a one of main inputs, effects on the economic growth; in other words, on the base of some optimistic new economic growth models, the uncertainty through positive shocks positively effects on the economic growth. So, to find some evidences about it, in this research we try to find experimentally direct effects of uncertainty of oil proved reserves on macroeconomics of Iran by using annually data from 1980 to 2013 by using Multivariate GARCH-in-mean VAR model. We find that uncertainty in oil proved reserves has not had statistically significant effect on aggregate output and the responses to positive and negative shocks are symmetric. Keywords: Uncertainty, Oil proved reserves, Time allocation of resources, Vector autoregression multivariate GARCH-in-mean VAR. JEL Classification: C32; E10; Q32.